2001
DOI: 10.1079/ber2001110
|View full text |Cite
|
Sign up to set email alerts
|

The effect of natural enemies on the spread of barley yellow dwarf virus (BYDV) by Rhopalosiphum padi (Hemiptera: Aphididae)

Abstract: The effects of two natural aphid enemies, adult Coccinella septempunctataLinneaus, a predator, and Aphidius rhopalosiphi de Stefani Perez, a parasitoid, on spread of barley yellow dwarf virus (BYDV) transmitted by the bird cherry–oat aphid, Rhopalosiphum padi (Linnaeus) were studied under laboratory conditions. Predators or parasitoids were introduced to trays of durum wheat seedlings and the patterns of virus infection were observed after two, seven and 14 days of exposure. More plants were infected with BYDV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 23 publications
2
59
0
2
Order By: Relevance
“…In our experiment, the increased dissemination of the plant pathogen was caused by the typical ''drop-and-move'' escape response of A. pisum to foraging predators, associated with a rapid scattering of the aphids from the central plant (see Losey and Denno 1998a;Braendle and Weisser 2001). In a similar study, Smyrnioudis et al (2001) found that adults of the parasitoid Aphidius rhopalosiphi de Stefani Perez did not increase the incidence of barley yellow dwarf virus in trays of wheat seedlings containing the aphid virus vector Rhopalosiphum padi L. Thus, the parasitoid-induced dispersal of the plant pathogen that we observed might be specific to certain parasitoid-aphid-host plant combinations, and is primarily dependent upon the escape response of the aphid vector rather than the presence of a particular form of foraging predator (see also Losey and Denno 1998b).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our experiment, the increased dissemination of the plant pathogen was caused by the typical ''drop-and-move'' escape response of A. pisum to foraging predators, associated with a rapid scattering of the aphids from the central plant (see Losey and Denno 1998a;Braendle and Weisser 2001). In a similar study, Smyrnioudis et al (2001) found that adults of the parasitoid Aphidius rhopalosiphi de Stefani Perez did not increase the incidence of barley yellow dwarf virus in trays of wheat seedlings containing the aphid virus vector Rhopalosiphum padi L. Thus, the parasitoid-induced dispersal of the plant pathogen that we observed might be specific to certain parasitoid-aphid-host plant combinations, and is primarily dependent upon the escape response of the aphid vector rather than the presence of a particular form of foraging predator (see also Losey and Denno 1998b).…”
Section: Discussionmentioning
confidence: 90%
“…Some herbivorous insects, including some species of aphids, employ a basic ''drop and move'' escape response to natural enemies and the presence of arthropod predators has sometimes been found to increase the incidence of plant disease by intensifying vector dispersion (Bailey et al 1995;Losey and Denno 1998a;Smyrnioudis et al 2001). With regard to insect parasitism, the behaviour of a parasitized host can be modified in various ways, and is often speculated to be associated with some ''adaptive value'' for the developing parasite or remaining host population (Brodeur and McNeil 1992;Poulin 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aphids are known vectors of many plant viruses so the qualitative effects of aphid-natural enemies interactions may indirectly impact plants by both mediating plant infestation rates by aphids and subsequently disease transmission in plants. Studies have shown that the dispersal response of aphids exposed to natural enemies that elicit strong antipredator behaviour, such as ladybird beetles (Coccinella califonica), is correlated with an increased spread of Bean Yellow Mosaic Virus (Roitberg & Myers 1978) and Barley Yellow Dwarf Virus (Smyrnioudis et al 2001). Adaptive movement of prey in response to predation is also thought to be an important factor in metapopulation dynamics (Abrams 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This experiment was designed as a ''top-down'' study, in which the experimental priority was to obtain the best data possible on the primary ecosystem property under study (in this case virus incidence). To avoid introducing artifact into the virus incidence data, we sampled the grass stands only once a year using minimally intrusive means, because disturbances can alter the movement of aphids in stands and thus alter patterns of B/CYDV infection (Bailey et al 1995;Smyrnioudis et al 2001). We then complemented this field experiment with two laboratory studies of mechanism in which we examined aphid host preferences and fecundity using the same E. glaucus and A. fatua, as well as other host species to evaluate the generality of our findings.…”
Section: Introductionmentioning
confidence: 99%